Primary school students' conceptions of history - (:unkn) unknown (ELSEVIER SCIENCE BV, 2009)
The aim of this qualitative case study is to define the primary school sixth grade students' views about the quality of history and their perception of history. The Interview Form which was prepared by expert opinions was used in the process of gathering the data. The data were collected from 29 students who are in sixth grade in Central district of Kastamonu city in Turkey and data were analyzed by descriptive analysis approach, content analysis approach and expressive analysis approach. For a great many of students, history means past times and concepts of the past times. For most of the students, the concept of history is equivalent to the concept of time. The students mostly believe that being a historian is being knowledgeable. 1/3 of them stated that anyone who wants to be a historian can be a historian. And less than 1/4 of these students, emphasized on change and continuity, which are fundamental concepts for history, and stated on the continuity of time and place. (C) 2009 Elsevier Ltd. All rights reserved
Keywords: Social Studies; history; history teaching; curriculum; historical consciousness